Strategy Analysis refers to Motivation in Learning - Yuliani; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Motivation to learn is a psychological factor that is non-intellectual and plays a role in fostering enthusiasm for learning for individuals. The influence of motivation on a person depends on how much motivation it is able to raise a person's motivation to various levels. Learning motivation is all efforts within oneself that give rise to learning activities, and ensure the continuity of learning activities and provide direction to learning activities so that the desired goals are achieved. There are two types of motivation, namely intrinsic motivation and extrinsic motivation. Strategies that can be used to foster motivation in learning include explaining learning objectives to students, giving prizes, creating rivals or competition, giving praise, applying pressure, forming good study habits, helping students with learning difficulties, both individually and in groups. , use varied methods, and use good media and must be in accordance with learning objectives